Terapi komplementer non invasif pada peningkatan status kesehatan sistem pernapasan penderita PPOK: Sebuah literature review - Senja Paramita; I Made Kariasa; Sri Yona (Holistik Jurnal Kesehatan, 2021)
Non-invasive complementary therapies in improving the health status of the respiratory system in patients with COPD: A literature review Background: Patients with COPD need an individual treatment plan that aims to cope with symptoms and requires a different and individualized treatment plan. The medication and surgery cause several complications, accompanied by negative side effects, the “one size fits all as a universal approach" is inappropriate in the treatment of COPD. Therefore, non-pharmacological therapy needed to complement and must be part of comprehensive COPD management as rehabilitation in patients with COPD.Purpose: A literature study was explore non-invasive complementary therapies in improving the health status of the respiratory system in patients with COPDMethod: Analysis based on articles from online databases Proquest, EBSCO, Cochrane, PubMed, and Google scholar. The criteria for the articles used are Randomized Controlled Trial (RCT), published in 2015-2020, in English, full text, accessible. The initial search found 875 articles, after going through the screening process, nine articles were found that were suitable and analyzed.Results: Five types of interventions were found in nine publications, namely physical exercise, breathing exercises, chest physiotherapy, hypnosis, and transcutaneous electrical nerve stimulation providing various benefits on status. Globally there are three million deaths every year. The prevalence of COPD is expected to increase over the next 40 years and by 2060 it is estimated that there will be more than 5.4 million deaths each year due to COPD.Keywords: Non-invasive; Complementary therapies; Health status; Respiratory system; COPDPendahuluan: Penderita PPOK membutuhkan rencana pengobatan individual yang bertujuan untuk menanggulangi gejala dan membutuhkan rencana penanganan yang berbeda dan bersifat individual. Mengingat penggunaan obat-obatan dan pembedahan menimbulkan banyak komplikasi dan disertai efek samping negative maka pendekatan “one size fits all” tidak cukup dalam pengobatan PPOK. Oleh karena itu, diperlukan terapi nonfarmakologis untuk melengkapi dan harus menjadi bagian dari manajemen PPOK yang komprehensif sebagai rehabilitasi pada penderita PPOK.Tujuan: Sebuah studi literatur untuk mengeksplorasi terapi komplementer non-invasif dalam meningkatkan status kesehatan sistem pernapasan pada pasien PPOKMetode: Analisa berdasarkan artikel yang berasal dari database online Proquest, EBSCO, Cochrane, PubMed, dan Google scholar. Kriteria artikel yang digunakan ialah Randomized Controlled Trial (RCT), diterbitkan pada tahun 2015-2020, berbahasa Inggris, teks lengkap, dapat diakses. Perncarian awal didapatkan 875 artikel setelah melalui proses penyaringan didapatkan sembilan artikel yang sesuai dan diananlisis.Hasil: Didapatkan lima macam intervensi dalam sembilan publikasi yang ditemukan yaitu physical exercise, latihan pernapasan, fisioterapi dada,  hipnosis, dan trancutaneus electrical nerve stimulation memberikan manfaat yang beragam pada status. Secara global terdapat tiga juta kematian setiap tahunnya. Prevalensi PPOK diperkirakan akan meningkat selama 40 tahun ke depan dan pada tahun 2060 diperkirakan akan ada lebih dari 5,4 juta kematian setiap tahun disebabkan oleh PPOK.